Global prediction of the vertical total electron content of the ionosphere based on GPS data - García-Rigo, A.; Monte, E.; Hernández-Pajares, M.; Juan, J. M.; Sanz, J.; Aragón-Angel, A.; Salazar, D. (Radio science, 2011)
Although vertical total electron content (VTEC) forecasting is still an open subject of research, the use of predictions of the ionospheric state at a scale of several days is an area of increased interest. A global VTEC forecast product for two days ahead, which is based exclusively on actual Global Positioning System (GPS) data, has been developed in the frame of the International Global Navigation Satellite Systems (GNSS) Service (IGS) Ionospheric Working Group (IGS Iono‐WG). The UPC ionospheric VTEC prediction model is based on the Discrete Cosine Transform (DCT), which is widely used in image compression (for instance, in JPEG format). Additionally, a linear regression module is used to forecast the time evolution of each of the DCT coefficients. The use of the DCT coefficients is justified because they represent global features of the whole two‐dimensional VTEC map/image. Also, one can therefore introduce prior information affecting the VTEC, for instance, smoothness or the distribution of relevant features in different directions. For this purpose, the use of a long time series of final/rapid UPC VTEC maps is required. Currently, the UPC Predicted product is being automatically generated in test mode and is made available through the main IGS server for public access. This product is also used to generate two days ahead preliminary combined IGS Predicted product. Finally, the results presented in this work suggest that the two days ahead UPC Predicted product could become an official IGS product in the near future. Key Points Two‐day ahead prediction model of global VTEC maps Based on the Discrete Cosine Transform (DCT) and a linear regression module Tests against Final UPC products and JASON VTEC measurements